СЕЛЕКЦІЯ НОВИХ ШТАМІВ БУЛЬБОЧКОВИХ БАКТЕРІЙ-СИМБІОНТІВ MELILOTUS ALBUS ТА TRIGONELLA FOENUM-GRAECUM - Логоша, О. В.; Воробей, Ю. О.; Усманова, Т. О. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2024)
Objective. Study the properties of effective strains of nodule bacteria-microsymbionts of white melilot (Melilotus albus) and fenugreek (Trigonella foenum-graecum). Methods. Microbiological, biochemical, vegetative experiment, statistical. Results. During 2016–2021, a search for active strains of nodule bacteria of rare types of leguminous plants was carried out. Analytical selection methods have found 11 strains of Ensifer sp. — microsymbionts of white melilot and 3 of fenugreek. It was shown that the inoculation of white melilot seeds with bacterial suspensions of new strains of Ensifer sp. BR-4 and BR-201 contribute to an increase in the formation of nodules on plant roots by 15 % and 24 % versus the positive control (inoculation with Ensifer meliloti ДН-15), as well as an increase in vegetative mass by 25 % and 39 %, respectively. It was also established that during seed inoculation with suspensions of Ensifer sp. G-6 and G-10, the number of nodules exceeded this indicator of the positive control by 52 % and 72 %, the increase in vegetative mass was 4 % and 25 %, respectively. The peculiarities of the growth of new effective strains of rhizobia on pea agar medium, meat-peptone and mannitol-yeast agar, litmus milk, the ability to assimilate various sources of carbon and nitrogen and resistance to antibiotics were studied. The differences in the nature of growth on MPA and assimilation of nitrogen and carbon sources for melilot and fenugreek rhizobia were shown. Based on the results of research into the cultural-morphological and physiological-biochemical properties of the new microsymbiont isolates of the white melilot and fenugreek, it was shown that they correspond to the properties of the reference strain and characteristics of E. meliloti species. Conclusion. Analytical selection methods were used to obtain new strains of microsymbionts of the white melilot and fenugreek. The positive effect of bacterization of the seeds of these cultures with bacterial suspensions of the obtained strains on the symbiotic activity and productivity of plants was established. According to the cultural-morphological and physiological-biochemical properties, the new isolates have been assigned to E. meliloti. Differences in the nature of growth on MPA and assimilation of carbon and nitrogen between the rhizobia of Melilotus albus and Trigonella foenum-graecum were revealed.